PROFIL KEMAMPUAN PENALARAN DEDUKTIF MAHASISWA PADA MATERI RUANG VEKTOR - Palupi Sri Wijayanti (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2017)
The aim of this is to determine the profile of students’ deductive reasoning ability on vector space chapter. Students’ deductive reasoning abilities must develop to enhance students’ experiences to prove a theorem that is often found in mathematics teaching and learning. Deductive reasoning is a process of reasoning that begins with the proof of specific statements to take a general conclusion. The type of this research is descriptive quantitative and qualitative. The research was conducted in the first of the year grade in mathematics education study program, PGRI University of Yogyakarta. The instruments of this research use a deductive reasoning test. Analysis of data use descriptive analysis in qualitative and quantitative. The quantitative data is used to find the mean, mode, and percentage of students' competencies. The qualitative data is used to show the categorization of students deductive reasoning ability. The results of this study is the profile of students deductive reasoning ability on vector space chapter is 21% is in low category, 46% is moderate category, and 33% high category.